Corporate Governance and Operations Performance: Inventory Study on Malaysian Listed Firms - Nadarajan, Santhirasegaran; Chandren, Sitraselvi; Bahaudin, Ahmad Yusni; Mohammed Elias, Ezanee; Mohd.Nawi, Mohd.Nasrun (International Journal of Supply Chain Management, 2015)
This paper reveals the relationship by developing a conceptual model that entails the relationship between corporate governance and operations performance from the angle of inventory management that’s include inventory value, inventory turnover and days of supply as the performance measure. What makes this study difference from other study? Most study conducted by using accounting measures to see if corporate governance affect the firm’s performance but this study will discuss how inventory measures dictates the earlier study